IMPLEMENTASI PENDEKATAN SAINTIFIK DENGAN METODE ROLE PLAYING YANG DIMODIFIKASI PERMAINAN DOMINO PADA PEMBELAJARAN KURIKULUM 2013 - Budi Sasomo; Moh. Arif Hidayat (Jurnal Ilmiah Matematika dan Pendidikan Matematika, 2017)
The purpose of this paper was to examine the mathematics achievement of students who are subject to a scientific approach using role playing method and dominoes game. Based on the hypothesis testing using anava one way concluded with a scientific approach using role playing method and dominoes game got better achievement than classes that are subject to direct learning instruction. Thus the scientific approach using role playing method and dominoes game could be an alternative to learning mathematics for teacher who taught in the schools using the curriculum of 2013.